Pengaruh Model Pembelajaran Kooperatif Tipe STAD dengan Media Virtual Terhadap Kreativitas Fisika Peserta Didik - Nina Nisrina; Gunawan Gunawan; Ahmad Harjono; Hairunnisyah Sahidu (Indonesian, 2021)
Creativity is one of the essential competencies that should be developed in physics learning. However, conventional teacher-centered instruction has limited students' opportunities to develop their creativity. This study aimed to analyze the effect of the Student Teams Achievement Division (STAD) cooperative learning model assisted by a virtual laboratory on students' physics creativity in the topic of static fluids. This study employed a quasi-experimental method using a Nonequivalent Control Group Design. The sample consisted of one experimental class and one control class selected through purposive sampling. The research instrument was a verbal and figural creativity test that met the validity and reliability requirements. Data were analyzed using homogeneity testing, normality testing, hypothesis testing, and N-gain analysis. The results showed that the STAD cooperative learning model assisted by a virtual laboratory had a positive effect on students' physics creativity. Furthermore, the improvement in students' verbal and figural creativity in the experimental class was higher than that in the control class. Therefore, the STAD cooperative learning model assisted by a virtual laboratory can be used as an alternative approach to enhance students' creativity in physics learning.